Sex Differences in Primary HIV Infection: Revisiting the Role of TLR7-Driven Type 1 IFN Production by Plasmacytoid Dendritic Cells in Women - Guéry, Jean-Charles (Frontiers in Immunology, 2021)
Plasmacytoid dendritic cells (pDCs) produce type I interferon (IFN-I) during HIV-1 infection in response to TLR7 stimulation. However, IFN-I-signaling has been shown to play opposite effects in HIV-1 and SIV infection. TLR7-driven type I interferon production in pDCs is higher in women than in men due to the cell-intrinsic actions of estrogen and X-chromosome complement. Indeed, TLR7 is encoded on the X-chromosome, and TLR7 gene escapes X chromosome inactivation in immune cells of women which express significantly higher levels of TLR7 protein than the male cells. Following HIV infection, women have lower viremia during acute infection and exhibit stronger antiviral responses than men, which has been attributed to the increased capacity of female pDCs to produce IFN-a upon TLR7-stimulation. However, a deleterious functional impact of an excessive TLR7 response on acute viremia in women has been recently revealed by the analysis of the frequent rs179008 c.32A>T SNP of TLR7. This SNP was identified as a sex-specific protein abundance quantitative trait locus (pQTL) causing difference in TLR7 protein dosage and effector function in females only. T allele expression was associated with lower TLR7 protein synthesis, blunted production of IFN-a by pDCs upon TLR7 stimulation and unexpectedly lower viral load during primary HIV-1 infection in women. In the present review, I will revisit the role of TLR7-driven pDC innate function in the context of HIV-1 infection to discuss at what stage of primary HIV-1 infection, TLR7 rs179008 T allele is likely to be protective in women.